1997
DOI: 10.1111/j.1460-2695.1997.tb01535.x
|View full text |Cite
|
Sign up to set email alerts
|

THE INFLUENCE OF AGEING AT INTERMEDIATE TEMPERATURES ON THE MECHANICAL BEHAVIOUR OF A DUPLEX STAINLESS STEEL: Part II. FATIGUE LIFE AND FATIGUE CRACK GROWTH

Abstract: The mechanical behaviour of AISI 329 steel has been investigated for ageing times up to 20,000 h at temperatures of 475,425, 375, 325 and 275°C. The study has concentrated on the changes in the response to cyclic strains, in the low-and the high-cycle fatigue regimes, and in the resistance to fatigue crack propagation as a function of temperature and time of ageing.It is shown that ageing increases the fatigue resistance in the high-cycle fatigue regime, but the opposite occurs in the low-cycle fatigue regime.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
(8 reference statements)
1
6
0
Order By: Relevance
“…Fatigue crack propagation micro‐mechanisms have only scarcely been investigated. More numerous studies deal with FCGB in hot‐ or cold‐rolled duplex stainless steels containing larger amounts of ferrite (45–62%) 14–23 . It has been shown that, in these materials, the fatigue crack growth rate (FCGR) is increasing with thermal ageing and with the amount of ferrite and with the associated embrittlement.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Fatigue crack propagation micro‐mechanisms have only scarcely been investigated. More numerous studies deal with FCGB in hot‐ or cold‐rolled duplex stainless steels containing larger amounts of ferrite (45–62%) 14–23 . It has been shown that, in these materials, the fatigue crack growth rate (FCGR) is increasing with thermal ageing and with the amount of ferrite and with the associated embrittlement.…”
Section: Introductionmentioning
confidence: 99%
“…Microstructural effects have also been evidenced but all the authors do not agree on their origin. For instance, the frequency of crack deviations along the crack path can be either higher 13 , 20 or lower 9 in the unaged condition than in the aged condition. In wrought duplex stainless steels, Marrow and King 17 observed crack deviation at all interfaces for crack propagating perpendicularly to the elongated phases.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations